Penerapan Model Pbl (Problem Based Learning) Berbantuan Media Interaktif Untuk Meningkatkan Minat Dan Hasil Belajar Di Kelas X SMA Negeri 2 Medan - Leni Fauziah; Pandu Prabowo Warsodirejo; Hasda Tanty (Departement of Mathematics Education, 2024)
This research aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model assisted by interactive media in enhancing students' interest and learning outcomes in Mathematics, specifically on the topic of exponents in grade X of SMA Negeri 2 Medan. The applied PBL model is integrated with interactive media such as Wordwall and Canva. The use of these tools is intended to facilitate students in understanding abstract concepts in an engaging and interactive manner. The research results indicate an increase in students' interest and learning outcomes after the implementation of this method.